2004
DOI: 10.1051/lait:2004019
|View full text |Cite
|
Sign up to set email alerts
|

?-Caseinophosphopeptide (f1-25) confers on ?-casein tryptic hydrolysate an antioxidant activity during iron/ascorbate-induced oxidation of liposomes

Abstract: -Protein ingredients such as hydrolysates of milk proteins may improve the nutritive value of functional foods. For instance, β-casein tryptic hydrolysate could simultaneously increase iron absorption and prevent lipid oxidation in foods containing high contents of polyunsaturated fatty acids (PUFA). The aim of this study was to determine the antioxidant activity of β-casein tryptic hydrolysate and of its β-caseinophosphopeptide (f1-25) on Fe(III)/ascorbate-induced oxidation of muscle phospholipids in a liposo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 55 publications
0
23
0
1
Order By: Relevance
“…In the presence of Fe-␤ -CPP(1-25), MDA levels were as low as in the iron-deprived group. MDA levels were higher in cells grown with FeSO 4 and highest in cells grown with Fe-P (p ! 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the presence of Fe-␤ -CPP(1-25), MDA levels were as low as in the iron-deprived group. MDA levels were higher in cells grown with FeSO 4 and highest in cells grown with Fe-P (p ! 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Previous in vitro studies assessed the protective effect of cow's milk proteins and cow's milk-derived peptides on peroxidation [3,4] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it also has been suggested that CPPs could inhibit lipid oxidation by chelation with non-phosphorylated groups such as Glu and Asp, and/or via non-chelating mechanisms such as free radical scavenging (Kitts, 2005). Previous authors have shown that CPPs exhibit both primary and secondary antioxidant activities in aqueous (Chin & Kitts, 2004) and lipid emulsion systems (Diaz, Dunn, McClements, & Decker, 2003), in phosphatidylcholine liposome model systems (Kansci, Genot, Meynier, Gaucheron, & Chobert, 2004), and in beef homogenates (Diaz & Decker, 2004;Sakanaka, Tachibana, Ishihara, & Juneja, 2005). In contrast, the ability of CPPs to prevent the latter effects caused by oxidative stress in any biological system remains poorly understood and inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…β-Caseinophosphopeptide (β-CN 1-25 ) can also facilitate iron absorption and has antioxidant activity similar to that o fF e L f .I nc o n t r a s tt oF e L f ,t h es t r u c t u r e -function relationship of β-CN 1-25 is well characterized (Kansci et al 2004). The objective of this study was to extend our understanding of iron solubilization by Lf in the presence of bicarbonate anions to develop a manufacturing process and appropriate applications for FeLf.…”
mentioning
confidence: 99%